2013
DOI: 10.3389/fimmu.2013.00449
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3: An Activation Marker and Activation Limiter of Innate Immune Cells

Abstract: Tim-3 was initially identified on activated Th1, Th17, and Tc1 cells and induces T cell death or exhaustion after binding to its ligand, Gal-9. The observed relationship between dysregulated Tim-3 expression on T cells and the progression of many clinical diseases has identified this molecule as an important target for intervention in adaptive immunity. Recent data have shown that it also plays critical roles in regulating the activities of macrophages, monocytes, dendritic cells, mast cells, natural killer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
136
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 44 publications
6
136
1
2
Order By: Relevance
“…Tim-3, one of the most important members of this family, is primarily expressed in CD8 + T cells, monocytes, dendritic cells, and mast cells. Tim-3 is a specific surface marker of Th1 cells, and regulates autoimmune and allergic disease by mediating the immune response of Th1 cells (Han et al, 2013;Anderson, 2014). Furthermore, Tim-3 was found to be closely related to the occurrence and development of several types of cancer, including prostate cancer, non-small cell cancer, cervical cancer, and melanoma (Geng et al, 2006;Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tim-3, one of the most important members of this family, is primarily expressed in CD8 + T cells, monocytes, dendritic cells, and mast cells. Tim-3 is a specific surface marker of Th1 cells, and regulates autoimmune and allergic disease by mediating the immune response of Th1 cells (Han et al, 2013;Anderson, 2014). Furthermore, Tim-3 was found to be closely related to the occurrence and development of several types of cancer, including prostate cancer, non-small cell cancer, cervical cancer, and melanoma (Geng et al, 2006;Cao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of studies have shown that abnormal expression of Tim-3 is an important cause of autoimmune diseases, infections, transplantation problems and cancers. 24 Recent data have shown that NK cells can also be regulated by Tim-3. Tim-3 was found to act as a marker of activation or maturation of NK cells and suppress NK cell cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…40 TIM-3 plays important roles in the regulation of both arms of innate and adaptive immunity. 41,42 In tumors, TIM-3 expression is induced in innate immune cells, e.g., dendritic cells and macrophages, by tumor-released factors such as interleukin (IL)-10 and vascular endothelial growth factor, leading to a suppression of innate responses to nucleic acids released from apoptotic tumor cells by interacting with HMGB1. 44 Additionally, TIM-3 serves as an exhaustion marker for T cells in tumors.…”
Section: -16mentioning
confidence: 99%